Field emission properties of ta-C films with nitrogen doping - Park, KC; Moon, JH; Chung, SJ; Jung, JH; Ju, BK; Oh, MH; Milne, WI; Han, MK; Jang, J (AMER INST PHYSICS, 1997)
We have studied the electron emission characteristics of tetrahedral amorphous carbon (ta-C) films with different nitrogen content. With increasing N content in ta-C, the room-temperature conductivity as well as the emission current decreases and then increases, resulting in minima. The Fermi level shifts toward the conduction band and, thus, the work function decreases by N doping in ta-C, however, the emission currents of doped ta-C films are less than those of undoped ta-C. (C) 1997 American Vacuum Society.
Keywords: AMORPHOUS DIAMOND; CARBON